SAP97 regulates behavior and expression of schizophrenia risk enriched gene sets in mouse hippocampus. - Preetika Gupta; Ogul E Uner; Soumyashant Nayak; Gregory R Grant; Robert G Kalb (PLoS ONE, 2018)
Synapse associated protein of 97KDa (SAP97) belongs to a family of scaffolding proteins, the membrane-associated guanylate kinases (MAGUKs), that are highly enriched in the postsynaptic density of synapses and play an important role in organizing protein complexes necessary for synaptic development and plasticity. The Dlg-MAGUK family of proteins are structurally very similar, and an effort has been made to parse apart the unique function of each Dlg-MAGUK protein by characterization of knockout mice. Knockout mice have been generated and characterized for PSD-95, PSD-93, and SAP102, however SAP97 knockout mice have been impossible to study because the SAP97 null mice die soon after birth due to a craniofacial defect. We studied the transcriptomic and behavioral consequences of a brain-specific conditional knockout of SAP97 (SAP97-cKO). RNA sequencing from hippocampi from control and SAP97-cKO male animals identified 67 SAP97 regulated transcripts. As large-scale genetic studies have implicated MAGUKs in neuropsychiatric disorders such as intellectual disability, autism spectrum disorders, and schizophrenia (SCZ), we analyzed our differentially expressed gene (DEG) set for enrichment of disease risk-associated genes, and found our DEG set to be specifically enriched for SCZ-related genes. Subjecting SAP97-cKO mice to a battery of behavioral tests revealed a subtle male-specific cognitive deficit and female-specific motor deficit, while other behaviors were largely unaffected. These data suggest that loss of SAP97 may have a modest contribution to organismal behavior. The SAP97-cKO mouse serves as a stepping stone for understanding the unique role of SAP97 in biology.